Penerapan Pembelajaran Pendidikan Agama Kristen Berbasis Amsal 3:5-6 dalam Meningkatkan Spiritualitas Siswa - Gustinilai Fau; Maria Theresia Teflopo (Sekolah Tinggi Teologi Sriwijaya, 2026)
This study examines Christian Religious Education (CRE) learning based on Proverbs 3:5-6 as an effort to strengthen students’ spirituality amid the challenges of the digital era. The study is motivated by the weakening internalization of spiritual values, moral crises among students, and the tendency of CRE learning to focus primarily on cognitive and theoretical aspects. The objective of this study is to analyze the theological relevance of Proverbs 3:5-6 and synthesize its application within CRE learning to support students’ spiritual formation. This research employs a qualitative approach using library research by analyzing books, scholarly articles, and relevant theological sources. The novelty of this study lies in the development of a conceptual CRE learning framework that integrates the two central principles of Proverbs 3:5-6, namely “trust in the Lord with all your heart” and “lean not on your own understanding,” as reflective and contextual pedagogical foundations. The literature synthesis indicates that these values are relevant for fostering spiritual maturity, moral character, self-control, and students’ ability to face spiritual challenges in the digital age. The findings suggest that integrating the theological principles of Proverbs 3:5-6 can provide a conceptual contribution to the development of CRE learning that emphasizes students’ spiritual transformation.